Landing pattern modification to improve patellofemoral pain in runners: A case series - Cheung, R. T. H.; Davis, I. S. (Journal of Orthopaedic & Sports Physical Therapy, 2011)
STUDY DESIGN: Case series. BACKGROUND: Patellofemoral pain is a common overuse injury in runners. Recent findings suggest that patellofemoral pain is related to high-impact loading associated with a rearfoot strike pattern. This case series describes the potential training effects of a landing pattern modification program to manage patellofemoral pain in runners. CASE DESCRIPTION: Three female runners with unilateral patellofemoral pain who initially presented with a rearfoot strike pattern underwent 8 sessions of landing pattern modification program using real-time audio feedback from a force sensor placed within the shoe. Ground reaction forces during running were assessed with an instrumented treadmill. Patellofemoral pain symptoms were assessed using 2 validated questionnaires. Finally, running performance was measured by self-reported best time to complete a 10-km run in the previous month. The runners were assessed before, immediately after, and 3 months following training. OUTCOMES: The landing pattern of runners was successfully changed from a rearfoot to a nonrearfoot strike pattern after training. This new pattern was maintained 3 months after the program. The vertical impact peak and rates of loading were shown to be reduced. Likewise, the symptoms related to patellofemoral pain and associated functional limitations were improved. However, only 1 of the participants reported improved running performance after the training. DISCUSSION: This case series provided preliminary data to support further investigation of interventions leading to landing pattern modification in runners with patellofemoral pain.